2014
DOI: 10.1021/ja410647c
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular and Lateral Intermolecular Hole Transfer at the Sensitized TiO2 Interface

Abstract: Characterization of the redox properties of TiO2 interfaces sensitized to visible light by a series of cyclometalated ruthenium polypyridyl compounds containing both a terpyridyl ligand with three carboxylic acid/carboxylate or methyl ester groups for surface binding and a tridentate cyclometalated ligand with a conjugated triarylamine (NAr3) donor group is described. Spectroelectrochemical studies revealed non-Nernstian behavior with nonideality factors of 1.37 ± 0.08 for the Ru(III/II) couple and 1.15 ± 0.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 55 publications
5
78
0
Order By: Relevance
“…In retrospect, the term "conduction band" was unfortunate as it was unclear whether the redox active states in TiO 2 were conduction band electrons or electrons trapped in surface states (perhaps as localized Ti(III) states) residing energetically within the forbidden energy gap; however, a more recent study indicated that conduction band electrons were indeed involved. 46 In any event, the data provided evidence that the redox active states in TiO 2 were important to the Ru(dcbq 0/− ) self-exchange. The reduction of the coordinated dcbq ligand occurred at more positive potentials than does TiO 2 reduction such that electrons injected into TiO 2 from vibrationally hot excited states were trapped on ground-state sensitizers, producing long-lived states that recombined through selfexchange reactions that are described further below.…”
Section: Direct Evidence For Self-exchange Energymentioning
confidence: 84%
See 1 more Smart Citation
“…In retrospect, the term "conduction band" was unfortunate as it was unclear whether the redox active states in TiO 2 were conduction band electrons or electrons trapped in surface states (perhaps as localized Ti(III) states) residing energetically within the forbidden energy gap; however, a more recent study indicated that conduction band electrons were indeed involved. 46 In any event, the data provided evidence that the redox active states in TiO 2 were important to the Ru(dcbq 0/− ) self-exchange. The reduction of the coordinated dcbq ligand occurred at more positive potentials than does TiO 2 reduction such that electrons injected into TiO 2 from vibrationally hot excited states were trapped on ground-state sensitizers, producing long-lived states that recombined through selfexchange reactions that are described further below.…”
Section: Direct Evidence For Self-exchange Energymentioning
confidence: 84%
“…At TiO 2 interfaces, the electric field contributions appear to be most significant; however, the number of experimental studies remains quite limited and deserves further study. 46,53 Light-Driven Self-Exchange. There have been several occasions where lateral self-exchange reactions were initiated with light.…”
Section: Direct Evidence For Self-exchange Energymentioning
confidence: 99%
“…A further complication is that observed rate constants may not unambiguously report on the interfacial electron transfer of interest 18 . The acute sensitivity of this reaction to the number of TiO 2 electrons present in the nanocrystallite 17 and the very weak driving-force dependence reported by most [19][20][21][22] , but not all 23 , has led many to conclude that observed rate constants report only on the diffusional encounters of the TiO 2 electrons with the molecular acceptors [24][25][26][27] . Clifford et al found that interfacial electron transfer was most easily understood when the physical location of the acceptor frontier molecular orbitals was taken into account 19 , which has been exploited to optimize interfacial electron transfer with highly doped degenerate semiconductors 28 .…”
mentioning
confidence: 99%
“…S9 and S10) HOMO-LUMO becomes well separated. Thus, both the charge and hole are transferred as per Scheme S1a, 47,48 rather than Scheme S1b (suggests a high chance of charge recombination), 49 and suggests a longer life time of the ejected electron placed at the SiO2 moiety. The expected spectral lines for this kind of charge/hole transfer occurs at the UV-vis range (3.18 (392.6 nm), 3.59 (348 nm), 1.99 (835.2 nm), 1.73 (724.5 nm), 2.5 (483.9 nm), 1.74 (720.3 nm) eV) corresponding to their HOMO-LUMO band gap (Fig.…”
Section: Elucidation Of Compositionmentioning
confidence: 99%